Pengujian Karakteristik Alat Ukur Radiasi Dose Calibrator Menggunakan Sumber Teknesium-99m di Instalasi Kedokteran Nuklir Rumah Sakit Abdoel Wahab Sjahranie Samarinda - Mutmainna, Fahira Mutya; Wardani, Pratiwi Sri; Putri, Erlinda Ratnasari; Zurma, Retno (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2024)
Dose Calibrator is one of the dosimeters used to measure radionuclide activity before being given to patients. In order to function as a radiation dosimeter, the dose calibrator must have several good dosimeter properties such as precision and stability. To test the dose calibrator, a source used by the hospital is required. One isotope that is widely used in the field of nuclear medicine, namely Tc-99m. The research steps this time are: firstly the elution performed by radiopharmaceuticals, secondly measuring background activity (background), thirdly calling for Tc-99m sources, fourthly measuring Tc-99m activity, fifthly calculating Tc-99m activity for testing precision, and sixth evaluate the results. Based on the research results on the precision test, it was found that the measurement results for the Tc-99m source were obtained at 0.578%. It can be concluded that the Capintec CRC 25R dose calibrator has good characteristics and performance, so that the measurement results can be trusted.